Impact of a pharmacist-led intervention on post-splenectomy vaccination adherence among trauma patients. (October 2020) - Scherrer, Leigh Ann; Benns, Matthew V; Frick, Christine; Pentecost, Karina; Broughton-Miller, Kimberly; Wojcik, Jodi; Frisbie, Michelle; Nice, Laura
Background: Patients who undergo splenectomy are at increased risk of infection caused by encapsulated bacteria. The Advisory Committee on Immunization Practices recommends a series of vaccinations for asplenic patients, the first of which are generally completed prior to hospital discharge in the setting of trauma. However, studies suggest that trauma patients receive booster vaccinations at a suboptimal rate. The aim of this study was to evaluate the impact of an inpatient, pharmacist-led post-splenectomy counseling service on patient understanding and patient-reported revaccination follow-up rate. Methods: Patients who underwent splenectomy due to trauma between October 2017 and February 2019 were surveyed via telephone questionnaire at least eight weeks after initial vaccination. Responses were compared to historical data which was collected prior to the service implementation. The primary outcome was patient reported follow-up vaccination rate. Secondary outcomes included patient awareness of vaccine requirements and need for rehospitalization. Results: A total of 67 patients met inclusion criteria, of whom 31 (46%) were successfully contacted by phone. After implementation of the post-splenectomy counseling service, 14 patients (45.2%) reported receiving second doses of pneumococcal and meningococcal vaccines, compared to 6 patients (6.3%) in the pre-implementation cohort ( p = 0.000001). Twenty-eight patients (90%) of the patients in the post-implementation cohort acknowledged awareness of the need for additional vaccines, whereas 44 (46%) of patients in the pre-implementation cohort acknowledged awareness ( p = 0.000043). Conclusion: A post-splenectomy counseling service led to improved rates of patient reported adherence to booster vaccines, as well as increased awareness for need to revaccinate.